UPAYA PENINGKATAN KETERAMPILAN KOLABORASI PESERTA DIDIK DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) - Rachmawati, Novita Ayu; Purwati, Arlin Sri; Sudibyo, Elok (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Education is certainly very important for the progress of a country. Therefore, the education obtained is certainly not only in cognitive knowledge, but other knowledge as well. This knowledge is such as communication skills, critical thinking, problem-solving, collaboration, metacognition, information literacy, creation, innovation and other skills. This skill is certainly useful as a guide for students in learning activities and in daily life. The purpose of this study is to improve students' collaboration skills in science learning. The method used is classroom action with a lesson study model. The stages of this model are designing learning (plan), implementing learning (do and see), then reflection and follow-up. This research was conducted during 3 learning cycles with different learning designs. The results of this study show that there is an increase in the collaboration skills of grade VII students of SMP Negeri 1 Porong from cycles 1, 2, and 3. This shows that the actions taken are successful and able to make students collaborate very well.